Legal Obligations of Corporate Social Responsibility as Efforts to Improve the Image of Islamic Banking in Indonesia - Hidayat, Asep Syarifuddin; Disemadi, Hari Sutra; Al-Fatih, Sholahuddin; Maggalatung, A Salman; Yunus, Nur Rohim (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
: This study aims to identify and analyze Islamic banking policies in maintaining and even improving the image/reputation of Islamic banking and to contribute scientifically to CSR in Islamic banking based on national law and Islamic law. This study uses a qualitative normative legal research method with a conceptual, statutory, and sociological approach. The results of this study indicate that the image or reputation of Islamic banking is the beliefs or feelings of consumers or stakeholders about Islamic banking itself. The reputation of Islamic banking is respect, assessment, and even appreciation from consumers or stakeholders. Islamic banking in improving its image or reputation can be done through CSR. This study provides a descriptive picture of Islamic banking, in general, to provide quality programs through CSR. CSR activities by several examples of Islamic banking in Indonesia refer to the company's obligation to protect and contribute to the community and stakeholders where the company is located. The concept of CSR in Islam is implemented in 3 (three) models of responsibility, namely the relationship of responsibility to Allah SWT; responsibility to humans; and responsibility to the natural environment. The concept of CSR in Islamic banking is a necessity that needs to be implemented as a form of responsibility towards fellow humans and the environment.